2021
DOI: 10.3390/nano11092347
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of MoP-RuP2 with Abundant Interfaces to Boost Hydrogen Evolution Reactions in Alkaline Media

Abstract: Exploiting efficient electrocatalysts for hydrogen evolution reactions (HERs) is important for boosting the large-scale applications of hydrogen energy. Herein, MoP-RuP2 encapsulated in N,P-codoped carbon (MoP-RuP2@NPC) with abundant interfaces were prepared via a facile avenue with the low-toxic melamine phosphate as the phosphorous resource. Moreover, the obtained electrocatalyst possessed a porous nanostructure, had abundant exposed active sites and improved the mass transport during the electrocatalytic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…For the localized hybridization strategy, our group designed MoP quantum dots on CoP/Cu 3 P nanowires (MoP/CoP/Cu 3 P), which served as a highefficiency HER electrocatalyst. 163 It needed a low overpotential of 64.6 mV to acquire 10 mA cm −2 with a low Tafel slope value of 68.2 mV dec −1 in 1 M KOH. The experimental results showed that the decoration of MoP quantum dots on the CoP/Cu 3 P nanowires has endowed the electrocatalyst with larger electrochemical surface area and more reactive sites.…”
Section: Localized Hybridizationmentioning
confidence: 99%
See 2 more Smart Citations
“…For the localized hybridization strategy, our group designed MoP quantum dots on CoP/Cu 3 P nanowires (MoP/CoP/Cu 3 P), which served as a highefficiency HER electrocatalyst. 163 It needed a low overpotential of 64.6 mV to acquire 10 mA cm −2 with a low Tafel slope value of 68.2 mV dec −1 in 1 M KOH. The experimental results showed that the decoration of MoP quantum dots on the CoP/Cu 3 P nanowires has endowed the electrocatalyst with larger electrochemical surface area and more reactive sites.…”
Section: Localized Hybridizationmentioning
confidence: 99%
“…The Co/Co 2 P interface efficiently favored the electron transfer from Co to Co 2 P and resulted in the shift of d‐band center to a higher level. For the localized hybridization strategy, our group designed MoP quantum dots on CoP/Cu 3 P nanowires (MoP/CoP/Cu 3 P), which served as a high‐efficiency HER electrocatalyst 163 . It needed a low overpotential of 64.6 mV to acquire 10 mA cm −2 with a low Tafel slope value of 68.2 mV dec −1 in 1 M KOH.…”
Section: Various Defects In Electrocatalystsmentioning
confidence: 99%
See 1 more Smart Citation